On-Demand Printing - Lee, Benjamin L. (DESIDOC Journal of Library & Information Technology, 2003)
Based on the emerging technologies such as electronic imaging technology, data storage and retrieval technology, and network technologies, the publishing world will employ integrated, open, intelligent, on-demand, and just-in-time systems. http://dx.doi.org/10.14429/dbit.23.1.3588